1996
DOI: 10.1152/jn.1996.76.6.4040
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and motor processing stages identified in the activity of macaque frontal eye field neurons during visual search

Abstract: 1. The latency between the appearance of a popout search display and the eye movement to the oddball target of the display varies from trial to trial in both humans and monkeys. The source of the delay and variability of reaction time is unknown but has been attributed to as yet poorly defined decision processes. 2. We recorded neural activity in the frontal eye field (FEF), an area regarded as playing a central role in producing purposeful eye movements, of monkeys (Macaca mulatta) performing a popout visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
599
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(654 citation statements)
references
References 49 publications
50
599
3
2
Order By: Relevance
“…A more direct evidence of concurrent motor preparation can only be revealed by physiological studies that can demarcate neural activity specifically linked to the generation of a saccade. In our mind, such motor preparation may correspond to the activity of movement-related cells in the frontal eye fields (Bruce and Goldberg 1985;Thompson et al 1996), superior colliculus (Dorris et al 1997;Munoz and Wurtz 1995;Paré and Hanes 2003), and possibly the lateral intraparietal cortex (Mazzoni et al 1996). However, we presume that such motor preparation, if not sufficiently advanced, is not necessarily a commitment to make a saccade and hence may not include the presaccadic burst activity described in superior colliculus.…”
Section: Parallel Programming During Error Correctionmentioning
confidence: 90%
See 1 more Smart Citation
“…A more direct evidence of concurrent motor preparation can only be revealed by physiological studies that can demarcate neural activity specifically linked to the generation of a saccade. In our mind, such motor preparation may correspond to the activity of movement-related cells in the frontal eye fields (Bruce and Goldberg 1985;Thompson et al 1996), superior colliculus (Dorris et al 1997;Munoz and Wurtz 1995;Paré and Hanes 2003), and possibly the lateral intraparietal cortex (Mazzoni et al 1996). However, we presume that such motor preparation, if not sufficiently advanced, is not necessarily a commitment to make a saccade and hence may not include the presaccadic burst activity described in superior colliculus.…”
Section: Parallel Programming During Error Correctionmentioning
confidence: 90%
“…Such a pattern of responses has led to the hypothesis that the corrective saccade may be programmed in parallel with the erroneous saccade (Becker and Jurgens 1979;McPeek et al 2000;Ray et al 2004). However, because saccade programming is composed of at least two stages, a visual stage that identifies the location of a target and a motor stage that prepares and executes the oculomotor command (Hooge and Erkelens 1996;Ludwig et al 2005; Thompson et al 1996;Viviani 1990), the extent to which parallel processing of correction may occur in anticipation of an error is still not clear in double-step tasks.…”
Section: Introductionmentioning
confidence: 99%
“…As in the main experiment, the patterns were perturbed with temporal orientation and contrast noise. After a variable delay (4,8,16,32, and 64 frames, corresponding to ∼47, 94, 188, 376, and 753 ms), a peripheral pattern appeared straight up from the fixated pattern (i.e., in the 90°location in Fig. 2).…”
Section: Methodsmentioning
confidence: 98%
“…For example, extreme noise values drawn from the tails of the distribution are more likely to generate errors in tilt discrimination than noise values closer to the mean. Our analysis here is similar to that used in single-cell neurophysiology to quantify the extent to which single neurons can distinguish between two stimuli (where distributions of firing rates are frequently nonnormal) (30)(31)(32).…”
Section: Temporal Integration Windows For Foveal Analysis and Peripheralmentioning
confidence: 99%
“…Altogether, these results suggest the implication of an attentional component to the target selection deficit in the contralesional hemifield. Interestingly, in the FEF, where neuronal responses during search tasks have been related to target selection, it has been shown that the visual selection process can be dissociated from saccadic response selection in the activity of visually responsive neurons (Thompson et al, 1996;Murthy et al, 2001). This suggests that LIP may participate in parallel with the FEF in both covert and overt orienting during visual search.…”
Section: Visual Searchmentioning
confidence: 99%